Altering management decisions with gained anatomical insight from a 3D printed model of a complex ventricular septal defect. (21st November 2016) - Bhatla, Puneet; Mosca, Ralph S.; Tretter, Justin T.
Abstract: Rapid prototyping is quickly gaining utility in various complex forms of CHD. In properly selected cases, these printed models provide detailed anatomical understanding that help guide potential surgical and cardiac catheterisation interventions. We present a case of a tunnel-like ventricular septal defect referred for surgical repair, where the decision to obtain a three-dimensional printed model helped in better understanding of the anatomy, leading to delaying, and hopefully avoiding altogether, surgical repair.